REGULATORY GENOME IN ADAPTATION, EVOLUTION, DEVELOPMENT, AND DISEASE - SMITH, MOYRA (ELSEVIER ACADEMIC PRESS, 2023)
The Regulatory Genome in Adaptation, Evolution, Development, and Disease synthesizes insights from recent genomic and gene expression studies across organisms, from humans to plants, animals, and single cell life, exploring common roles gene regulation plays in adaptive evolution, developmental biology and susceptibility to disease. The book sheds light on gene regulation across evolutionary timelines, illuminating new areas of focus and future research. Chapters consider key elements in gene expression regulation, fundamentals of genomic alterations over time, and in response to environmental and local conditions, epigenetics in adaptive evolution, and adaptive gene regulation in healthy processes and developmental biology, and in disease biology. Throughout the book, a comparative approach is adopted across organisms to highlight common evolutionary themes and genome diversity revealed by recent sequencing and GWAS studies, as well as how this informs our understanding of human adaptive evolution. The book finishes by detailing how we can use this knowledge to impact disease outcomes and healthy human metabolism, development, and physiology.